Bioresorbable electrodes in implantable electronic healthcare devices - Đorđević, Bogdana; Baraban, Larysa; Janićijević, Željko (Frontiers in Bioengineering and Biotechnology, 2025)
Implantable electronic devices for local in vivo monitoring of health parameters are an invaluable supplement to traditional diagnostic tools, offering real-time and personalized assessment. Such devices can be used to deliver different formats of patient-tailored treatment via controlled drug delivery or targeted stimulation. While non-degradable electronic healthcare devices are often challenging to interface with soft tissues and introduce risks associated with surgical extraction procedures, bioresorbable electronics–electronics that is safely decomposed and physiologically absorbed in the human body–undergoes controlled degradation and thus offers a promising approach for temporary monitoring and therapy. The crucial components of temporary bioelectronics are bioresorbable electrodes–electrically conductive interfaces that can be safely resorbed in the body–that should provide seamless integration with surrounding tissues, reliable functionality, and sufficient electromechanical integrity during their operational lifetime. Such electrodes find use as physical and chemical sensing elements, stimulator interfaces, and drug delivery modulators. Advances in materials science have led to significant milestones, such as 1) highly localized electrode-tissue interfacing, 2) monitoring of moving organs and less invasive implantation, and 3) electrochemical sensing with interference and degradation compensation. Additionally, integrated bioresorbable power sources and photo- or acoustically induced modulation have obviated the need for physical interconnects with external components. This mini review provides core insights into the emerging applications of bioresorbable electrodes for sensors, electroceuticals, and multifunctional devices combining sensing with electrotherapy, optogenetic stimulation, and/or drug delivery. We focus on application-specific materials selection and discuss the perspectives for improving the design and development of bioresorbable electronic healthcare devices.